Implementasi Program Shalat Dhuha sebagai Dakwah di SMK Pertiwi Rejang Lebong: Dampaknya Terhadap Pembentukan Karakter Siswa - Efi Hazizah; Citra Melia Utari (GHAITSA : Islamic Education Journal, 2025)
School as an educational environment has an important role in instilling religious, ethical, and human values to students. One of the activities that can integrate these values is da'wah, which can be made part of the educational process at school. This study aims to examine the process of implementing dhuha prayer and its impact on student character at Pertiwi Rejang Lebong Vocational High School (SMK). The approach used in this research is qualitative with the type of field research. Data were collected through observation, in-depth interviews, and documentation involving resource persons from students, teachers, and school administrators. The data analysis technique used is qualitative descriptive analysis. The results showed that SMK Pertiwi Rejang Lebong has implemented the dhuha prayer program as part of the da'wah activities that are routinely carried out at school. This program not only includes the implementation of dhuha prayer, but is also supported by Al-Qur'an deepening activities and religious lectures. The impact of this activity can be seen in the increase in discipline, strengthening of religious values, and positive character building among students. This research is expected to contribute to the development of a faith-based education model in a vocational school environment.